Indeks Kepuasan Masyarakat (IKM) terhadap Program TJSL PLN IP Jeranjang - Yanuar Ardiansyah; Putu Bagus Dandy A. B; Yunisetya Ariwibawa; Teguh Budiyanto; Tristiayu Permata D (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to measure the level of community satisfaction with the Corporate Social and Environmental Responsibility (TJSL) program of PLN IP UBP Jeranjang entitled “SENTRAL: National People’s Weaving Economy Center of Lombok.” The research employs an exploratory survey method using a Likert scale questionnaire (1–4), referring to the Permen PAN RB No. 14 of 2017 concerning Guidelines for Community Satisfaction Surveys on Public Service Delivery. The exploratory survey was chosen to capture respondents’ perspectives on aspects of program planning, human resources/officers/facilitators, implementation, and evaluation. The result of the Community Satisfaction Index (IKM) for the SENTRAL program was 3.22, or a converted IKM value of 80.38, categorized as grade B (Good). The highest scores, in order, were achieved in planning (3.40), evaluation (3.30), implementation (3.10), and human resources (3.06). These findings provide recommendations for PLN IP UBP Jeranjang to further improve the quality of its TJSL program to better meet community expectations. This research is also expected to offer insights for future studies on community satisfaction with TJSL programs.